The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1353/lan.2001.0074
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in Interaction: The Case of actually

Abstract: One aspect of the relationship between meaning and interaction is explored here by taking the English particle actually, which is characterized by flexibility of syntactic position, and investigating its use in a range of interactional contexts. Syntactic alternatives in the form of clause-initial or clause-final placement are found to be selected by reference to interactional exigencies. The temporally situated, contingent accomplishment of utterances in turns and their component turnconstructional units show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(101 citation statements)
references
References 41 publications
(15 reference statements)
1
95
0
4
Order By: Relevance
“…Modellen for faktisk's dialogiske funktion peger på at det danske faktisk har visse paralleller med fx engelsk actually (fx Smith & Jucker (2000) og Clift (2001)), og hollandsk eigenlijk (Plug 2005). Som den eneste af disse forfattere har Plug set på om forskellige dialogiske funktioner korrelerer med mere eller mindre distinkt udtale, og fundet at eigenlijk er staerkt reduceret (monosyllabisk) når det er del af en ytring der sigter på at korrigere talers egen tidligere diskurs, og ekspanderet (bi-og trisyllabisk) når det bruges til at påpege problemer i modtagers diskurs (2005: 137).…”
Section: Modsaetn Til Det Tilsyneladende Forhold Olgn)"unclassified
“…Modellen for faktisk's dialogiske funktion peger på at det danske faktisk har visse paralleller med fx engelsk actually (fx Smith & Jucker (2000) og Clift (2001)), og hollandsk eigenlijk (Plug 2005). Som den eneste af disse forfattere har Plug set på om forskellige dialogiske funktioner korrelerer med mere eller mindre distinkt udtale, og fundet at eigenlijk er staerkt reduceret (monosyllabisk) når det er del af en ytring der sigter på at korrigere talers egen tidligere diskurs, og ekspanderet (bi-og trisyllabisk) når det bruges til at påpege problemer i modtagers diskurs (2005: 137).…”
Section: Modsaetn Til Det Tilsyneladende Forhold Olgn)"unclassified
“…Une première stratégie consiste à se focaliser sur une forme, ensuite explorée dans les séquences qui la caractérisent et les actions qu'elle contribue à effectuer : cela représente une manière de procéder alignée avec la tradition linguistique, permettant dans certains cas de revisiter le traitement fonctionnel qui en a été proposé par elle (cela a été privilégié par les travaux sur les connecteurs et marqueurs linguistiques, comme « actually », Clift, 2001 ;« obwohl » Günther, 1999 ; en français « ben » ou « voilà » Bruxelles et Traverso, 2001, Groupe ICOR, 2008« attends », Groupe ICOR 2007, ou par les travaux sur certaines constructions syntaxiques, comme en français les dislocations à gauche, Fornel, 1988, Pekarek, 2001 ou la dislocation à droite, Horlacher, 2008).…”
Section: Développements Ultérieursunclassified
“…As it is the only case of matched pre-pivot and post-pivot talk in the data-set, any analysis of its function will be necessarily speculative though certain relevant observations can be made by setting this case against analyses of other phenomena. Clift (2001) and Heritage & Raymond (2005) have shown that the differential placement of identical lexical items or strings within a TCU is responsive to different interactional exigencies: Clift (2001) found that placement of "actually" initially or finally in a TCU had different uses and consequences in talk-in-interaction; Her itage & Ra ymond (2005), workin g with a colle ctio n of s econd asse ss men ts found (amongst other things) that by placing an agreement token (e.g. "yes") after a confirmation upgrades the right to ass ess some particu lar referent.…”
Section: Assessmentsmentioning
confidence: 99%